Methadone maintenance therapy users’ knowledge of, and attitudes towards methadone maintenance therapy: A meta-analysis - Yee, A.; Loh, H.S.; Tan, J.T.; Tan, A.; How, M.Y. (Associazione per l'Utilizzo delle Conoscenze Neuroscientifiche a fini Sociali, 2017)
Background: Methadone maintenance treatment is effective against opioid dependence. Despite its efficacy, its onemonth dropout rate had been reported to be as high as 24%. Studies have associated poor treatment compliance with poor knowledge of and attitude towards treatment. Aim: Our meta-analysis aims to examine the topics of knowledge of and attitude to MMT. Methods: A total of 3,979 participants were recruited from 16 eligible studies, published from inception till August 2015, identified by searching through the PubMed, OVID, EMBASE and EBSCO databases. Results: Our study showed that participants generally had poor knowledge and experience of MMT, and poor attitudes to it. In 7 papers, associated factors of poor attitude to and knowledge of MMT were reported to include: no history of prior or current use of methadone, failure to provide sufficient information, excessive youth, including those who are still too young to qualify when initiating opioid use, depression or stress, admission to detoxification centres, and incarceration. Conclusions: Despite its methodological limitations, this meta-analysis may offer insight to clinicians about poor knowledge, attitudes and perceptions as factors contributing to poor treatment compliance and failure to provide solutions.